2022
DOI: 10.1001/jamanetworkopen.2021.46124
|View full text |Cite|
|
Sign up to set email alerts
|

Associations of Serum Folate and Vitamin B12 Levels With Cardiovascular Disease Mortality Among Patients With Type 2 Diabetes

Abstract: IMPORTANCEThe associations of serum folate and vitamin B 12 levels with cardiovascular outcomes among patients with type 2 diabetes (T2D) remain unclear. OBJECTIVE To investigate the associations of serum folate and vitamin B 12 levels with risk of cardiovascular disease (CVD) mortality among individuals with T2D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 45 publications
(74 reference statements)
1
44
0
Order By: Relevance
“…Notably, we found a protective effect of genetically predicted folate levels on the risk of T2DM, which further indicate the association in the observational study was causal. Several researches of folate supplementation reducing the incidence of T2DM also support this causal relationship ( 20 , 21 , 38 ). A clinical trial that included 6,185 diabetic patients found that folate supplementation in T2DM patients resulted in lower hcy levels and better glycemic control ( 39 ).…”
Section: Discussionmentioning
confidence: 79%
“…Notably, we found a protective effect of genetically predicted folate levels on the risk of T2DM, which further indicate the association in the observational study was causal. Several researches of folate supplementation reducing the incidence of T2DM also support this causal relationship ( 20 , 21 , 38 ). A clinical trial that included 6,185 diabetic patients found that folate supplementation in T2DM patients resulted in lower hcy levels and better glycemic control ( 39 ).…”
Section: Discussionmentioning
confidence: 79%
“…In total, 2833 adults with diabetes aged ≥ 20 were enrolled in the NHANES III (1988)(1989)(1990)(1991)(1992)(1993)(1994). The ascertainment of diabetes included a self-report of physician diagnosis, fasting plasma glucose level ≥ 7.0 mmol/L (126 mg/ dL), 75-g oral glucose tolerance test result ≥ 11.1 mmol/L (200 mg/dL), or glycated hemoglobin A1c (HbA1c) level ≥ 6.5% (48 mmol/mol) [19][20][21]. Participants without data on serum thyroid hormone levels (n = 615), TSH and total thyroxine (TT 4 ) levels outside the reference range (n = 266), those with a history of thyroid disease at baseline (n = 110), those lost to follow-up (n = 4), and those who self-reported as being pregnant (n = 8) were excluded from the study.…”
Section: Study Populationmentioning
confidence: 99%
“…In the Original Investigation titled “Associations of Serum Folate and Vitamin B 12 Levels With Cardiovascular Disease Mortality Among Patients With Type 2 Diabetes,” 1 published January 31, 2022, there were errors in panel B of the Figure; the unit of measure for serum B 12 should be picograms per milliliter. There was an error in the title of Table 3; the years of the National Health and Nutrition Examination Survey should be from 1999 through 2014.…”
mentioning
confidence: 99%
“…There was an error in the title of Table 3; the years of the National Health and Nutrition Examination Survey should be from 1999 through 2014. This article has been corrected …”
mentioning
confidence: 99%